2022
DOI: 10.3390/toxics10110693
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Toxic Heavy Metals in the Pellets of Owls: A Novel Approach for the Evaluation of Environmental Pollutants

Abstract: Massive quantities of unadvisable synthetic pesticides are used in modern agricultural industries in order to increase productivity to convene food demands. Wild birds are an excellent bio-indicator of environmental contaminations as pesticides and heavy metals are intentionally highly hazardous pollutants. Considerably, raptorial birds (owls) attract consumers in the food chain and food web because they have wider forager and foraging grounds. In the current investigation, owl pellets were used as a viable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
0
1
Order By: Relevance
“…Above 1.8 ppm of Cr has shown adverse effects in birds, but the present study did not observe harmful levels of Cr [29,52,57]. Compared to other studies worldwide, the level of Ni in the waterbirds studied was lower [58,59]. Studies have reported that Ni could affect the pigmentation in feathers and moulting mechanisms when the Ni concentration is exceeded in birds [15][16][17].…”
Section: Discussioncontrasting
confidence: 65%
“…Above 1.8 ppm of Cr has shown adverse effects in birds, but the present study did not observe harmful levels of Cr [29,52,57]. Compared to other studies worldwide, the level of Ni in the waterbirds studied was lower [58,59]. Studies have reported that Ni could affect the pigmentation in feathers and moulting mechanisms when the Ni concentration is exceeded in birds [15][16][17].…”
Section: Discussioncontrasting
confidence: 65%